Choosing Roles in a Duopoly for Endogenously Differentiated Products - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
The choice of the roles by firms in a differentiated duopoly is analysed, under both the assumption of full and non full market coverage. Under the first, it turns out that, due to the endogeneity of product differentiation, both firms would prefer to be price leader, contrarily to the results obtained by previous literature. Under the latter, it is possible to analyse both price and quantity competition. The consequences in terms of social welfare are also outlined.
Keywords: 330